Binding Free Energy Calculations of Nine FDA‐approved Protease Inhibitors Against HIV‐1 Subtype C I36T↑T Containing 100 Amino Acids Per Monomer. (29th January 2016) - Lockhat, Husain A.; Silva, José R. A.; Alves, Cláudio N.; Govender, Thavendran; Lameira, Jerônimo; Maguire, Glenn E. M.; Sayed, Yasien; Kruger, Hendrik G.
Abstract : In this work, have investigated the binding affinities of nine FDA‐approved protease inhibitor drugs against a new HIV‐1 subtype C mutated protease, I36T↑T. Without an X‐ray crystal structure, homology modelling was used to generate a three‐dimensional model of the protease. This and the inhibitor models were employed to generate the inhibitor/I36T↑T complexes, with the relative positions of the inhibitors being superimposed and aligned using the X‐ray crystal structures of the inhibitors/HIV‐1 subtype B complexes as a reference. Molecular dynamics simulations were carried out on the complexes to calculate the average binding free energies for each inhibitor using the molecular mechanics generalized Born surface area (MM‐GBSA) method. When compared to the binding free energies of the HIV‐1 subtype B and subtype C proteases (calculated previously by our group using the same method), it was clear that the I36T↑T proteases mutations and insertion had a significant negative effect on the binding energies of the non‐pepditic inhibitors nelfinavir, darunavir and tipranavir. On the other hand, ritonavir, amprenavir and indinavir show improved calculated binding energies in comparison with the corresponding data for wild‐type C‐SA protease. The computational model used in this study can be used to investigate new mutations of the HIV protease and help in establishing effective HIV drug regimes and may also aid in future protease drug design. Abstract : This new C‐SA PR‐mutated strain (I36T↑T) involves mutations and an insertion to produce 100 amino acids in the PR enzyme. The patient from which this PR was isolated was completely drug naïve with respect to protease inhibitors. We have extended an existing computational model to provide a molecular understanding of the reduced inhibition characteristics of existing HIV PR drugs towards the new I36T↑T‐mutated PR.